Bibliometric Analysis Of Urban Drainage Flood Management - M. Alfi Wahyudi; Andri Irfan Rifai; Ade Jaya Saputra; Joewono Prasetijo (PT Publikasiku Academic Solution, 2024)
Floods are a frequent and challenging disaster, caused by factors such as heavy rainfall and improper waste disposal in drainage systems, leading to significant material and non-material losses. Effective measures are needed to mitigate flood impacts. This study uses bibliometric analysis to explore methods for flood disaster management, employing Publish or Perish software to filter relevant journals from Crossref. The data, including research titles, authors, publication years, and journal sources, is processed using VOSViewer software. The analysis shows that keywords like rainfall, drainage, and flood mitigation are central to the research, highlighting strong interconnections. The diversity of publishers and research types contributes to a global perspective, forming a solid research foundation. The study also tracks the growth of research on flood management in drainage channels from 2016 to 2023 and identifies diverse geographical case study regions. This analysis underscores the continued relevance and potential of this research to support effective global flood mitigation strategies.